Kombinasi Antioksidan Alami α-tokoferol dengan Asam Askorbat dan Antioksidan Sintetis BHA dengan BHT dalam Menghambat Ketengikan Kelapa Gongseng Giling (U Neulheu) selama Penyimpanan - Normalina Arpi (Agricultural Faculty, 2014)
Roasted coconut paste (Acehnese: u neulheu) containing high fat (± 70 %) which can cause rancidity. The purpose of this research is to determine the appropriate antioxidant, and the combination of antioxidants to inhibit rancidity of roasted coconut paste during storage. The experiment was conducted using a randomized block design (RBD) with 3 factors. Factor A is a combination of antioxidants, there are two levels ie α-tocopherol : ascorbic acid (A1), and BHA : BHT (A2). Factor K is the concentration of antioxidants, there are 3 levels ie 0.02 % : 0 % (K1), 0.01 % : 0.01 % (K2), and 0 % : 0.02 % (K3). Factor P is the storage time, there are two levels ie 0 months (P1) and 2 months (P2). The results showed that the antioxidant α-tocopherol, BHA, and BHT, singly or not combined, function equivalently to inhibit the increase of free fatty acids and peroxide number. All three of these antioxidants function better than ascorbic acid. Synergism effect was seen in ascorbic acid in combination with α-tocopherol, but not in BHA with BHT. After stored for 2 months, there were an increase (P≤0,01) in water content, acid number, and peroxide number of roasted coconut paste. Natural antioxidant α-tocopherol (0.02 %), the combination of α-tocopherol with ascorbic acid (0.01 % : 0.01 %), and the synthetic antioxidants BHA with BHT (single or in combination ) can inhibit fat oxidation and rancidity of roasted coconut paste up to 2 months of storage.